Multimodal and Translational Construction of MSME Marketing: An SFL-Based Analysis of Indonesian Coffee Catalogs at BRI EXPO 2025 - Eky Erlanda Edel; Ina Sukaesih; Rd. Safrina; Farizka Humolungo; Taufik Nur Hidayat (English Department - University of Sultan Ageng Tirtayasa, 2026)
In globalized markets, Micro, Small, and Medium Enterprises (MSMEs) must communicate product value and cultural identity effectively across linguistic and visual modes. This study examines how Indonesian coffee MSMEs construct promotional meaning through linguistic, translational, and multimodal strategies. The research analyzes promotional catalogs of 14 Indonesian coffee brands featured on the BRI UMKM Export platform. Using qualitative content analysis, the study integrates Systemic Functional Linguistics (SFL) to investigate the metafunctional structure of promotional language, translation analysis to examine meaning transfer between Indonesian and English texts, and multimodal discourse analysis to evaluate visual and material packaging design. The findings show that promotional discourse primarily constructs ideational meaning through origin claims, flavor descriptors, and production processes, while interpersonal meaning is conveyed through evaluative language that emphasizes quality and authenticity. Translation practices tend to prioritize terminological clarity and global intelligibility, with established equivalents dominating the translation strategies. The multimodal assessment further reveals strong visual identity and semiotic coherence across most brands, with average scores ranging from 3.2 to 4.6. Brands such as ToRi Coffee and ELS Coffee demonstrate particularly strong integration of cultural symbolism, visual aesthetics, and narrative storytelling. Overall, the study highlights the importance of integrating linguistic, translational, and multimodal resources to strengthen the global competitiveness of Indonesian MSME coffee products.